Functional characterization and allelic mining of OsGLR genes for potential uses in rice improvement - Zeng, Wei; Li, Hua; Zhang, Fanlin; Wang, Xinchen; Rehman, Shamsur; Huang, Shiji; Zhang, Chenyang; Wu, Fengcai; Li, Jianfeng; Lv, Yamei; Zhang, Chaopu; Li, Min; et al. (Frontiers in Plant Science, 2023)
Glutamate-like receptor (GLR) genes are a group of regulatory genes involved in many physiological processes of plants. With 26 members in the rice genome, the functionalities of most rice GLR genes remain unknown. To facilitate their potential uses in rice improvement, an integrated strategy involving CRISPR-Cas9 mediated knockouts, deep mining and analyses of transcriptomic responses to different abiotic stresses/hormone treatments and gene CDS haplotype (gcHap) diversity in 3,010 rice genomes was taken to understand the functionalities of the 26 rice GLR genes, which led us to two conclusions. First, the expansion of rice GLR genes into a large gene family during evolution had gone through repeated gene duplication events occurred primarily in two large GLR gene clusters on rice chromosomes 9 and 6, which was accompanied with considerable functional differentiation. Secondly, except for two extremely conserved ones (OsGLR6.2 and OsGLR6.3), rich gcHap diversity exists at the remaining GLR genes which played important roles in rice population differentiation and rice improvement, evidenced by their very strong sub-specific and population differentiation, by their differentiated responses to day-length and different abiotic stresses, by the large phenotypic effects of five GLR gene knockout mutants on rice yield traits, by the significant association of major gcHaps at most GLR loci with yield traits, and by the strong genetic bottleneck effects and artificial selection on the gcHap diversity in populations Xian (indica) and Geng (japonica) during modern breeding. Our results suggest the potential values of the natural variation at most rice GLR loci for improving the productivity and tolerances to abiotic stresses. Additional efforts are needed to determine the phenotypic effects of major gcHaps at these GLR loci in order to identify 'favorable' alleles at specific GLR loci specific target traits in specific environments to facilitate their application to rice improvement in future.